Delayed haemolytic transfusion reaction in adults with sickle cell disease: a 5‐year experience. (5th March 2015) - Vidler, Jennifer B.; Gardner, Kate; Amenyah, Kenneth; Mijovic, Aleksandar; Thein, Swee L.
Summary Delayed haemolytic transfusion reactions (DHTR) are potentially life‐threatening complications in patients with sickle cell disease (SCD). Between 1 August 2008 and 31 December 2013, 220 of 637 adult patients in our centre had at least one red blood cell (RBC) transfusion in 2158 separate transfusion episodes. Twenty‐three DHTR events occurred in 17 patients (13 female) including 15 HbSS, one HbSC and one HbSβ0 thalassaemia, equating to a DHTR rate of 7·7% of patients transfused. Mean interval from RBC transfusion to DHTR event was 10·1 ± 5·4 d, and typical presenting features were fever, pain and haemoglobinuria. Twenty of the 23 (87·0%) DHTR episodes occurred following transfusion in the acute setting. Notably, 11/23 (47·8%) of DHTRs were not diagnosed at the time of the event, most were misdiagnosed as a vaso‐occlusive crisis. 16/23 DHTRs had 'relative reticulocytopenia', which was more common in older patients. Seven of 23 episodes resulted in alloantibody formation, and three caused autoantibody formation. DHTRs are a severe but uncommon complication of RBC transfusion in SCD and remain poorly recognized, possibly because they mimic an acute painful crisis. Most of the DHTRs are triggered by RBC transfusion in the acute setting when patients are in an inflammatory state.